Desenvolvimento Regional e Imprensa: Estado da Arte e Perspectivas Teóricas - Fausto Cheida Curadi (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2019)
What is the relationship between Regional Development, as an area of knowledge, and the media, especially the press? Based on this question, this work aims to initiate a discussion that aims to relate the so-called “big press” to the Regional Development area, investigating its possible influence on the direction and choices of development patterns. For that, we first describe the genesis of regional thinking and its introduction in Brazil from the Graduate Programs. The purpose was to map the existing Graduate Programs in the country and to verify if in them the press was the object of researches at master’s or doctoral level. In a second moment, methodological possibilities for the study with the written press were approached. After the survey in a scope of 39 PPGs, the small number of 13 records was found between dissertations and theses that related Press and Regional Development. Thus, this article points out that it is necessary to increase studies in this area, since the media can not be disregarded as an agent involved in national and / or regional development processes.